C.E. Credit. Global Health in Dental Education: Establishing a Framework for Global Health Engagement Among Future Dental Practitioners - Noah Brady; Rachel Utomo; Aiysha Amjad; Anette Wu (Journal of the California Dental Association)
Background The COVID-19 Pandemic highlighted global health inequities, put a pause on short-term experiences in global health (STEGH’s), and emphasized new virtual modalities of international collaboration. In light of these new modes of collaboration, this article will reflect on and suggest changes to the current landscape of global health education in US dental schools.Results The authors suggest that existing global oral health engagements, which are predominantly STEGH’s, can be improved through adherence to guiding principles, such as those of the Brocher Declaration. Further, the authors argue that implementing global health didactics and internationalization of education into dental school curriculums would more optimally prepare students for participation in global health.Conclusions In summary, a shift in the introductory global health educational modality in dentistry, from the current STEGH-dominated model to a combination of formal didactics, internationalized education, and collaborative, sustainable, and interprofessional clinical experiences would strengthen both the future of global oral health and the field of dentistry altogether.Continuing Education Credit Available The practice worksheet is available online in the supplemental material tab for this article. A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20.